Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Expand.
Your answer should be a polynomial in standard form.
-p^2(p^2-p-1)=


Sagot :

Answer:

Step-by-step explanation:

Use distributive property. Then use exponent law.

Exponent law used here = [tex]a^{m}*a^{n}=a^{m+n}[/tex]

[tex]-p^{2}(p^{2} - p - 1) = -p^{2}*p^{2} - p *(-p^{2}) - 1*(-p^{2}) \\\\= -p^{4} + p^{3}+p^{2}[/tex]